1993
DOI: 10.1161/01.cir.88.4.1421
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and lipoproteins predicting coronary heart disease mortality and morbidity in patients with non-insulin-dependent diabetes.

Abstract: Our 7-year follow-up study gives evidence that low HDL and HDL2 cholesterol, high VLDL cholesterol, and high total and VLDL triglycerides are powerful risk indicators for CHD events in patients with NIDDM:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
130
1
3

Year Published

1996
1996
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(140 citation statements)
references
References 52 publications
6
130
1
3
Order By: Relevance
“…1,4 The prevalence of hypertriglyceridemia is three times higher in men with type 2 diabetes compared to men with normal glucose tolerance, 28 and high total and VLDL triglycerides are independent and powerful predictors of CHD in type 2 diabetes. 4,5 Indeed, type 2 diabetic patients with serum triglycerides above 2.3 mmolal have a 2-fold increased risk of CHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4 The prevalence of hypertriglyceridemia is three times higher in men with type 2 diabetes compared to men with normal glucose tolerance, 28 and high total and VLDL triglycerides are independent and powerful predictors of CHD in type 2 diabetes. 4,5 Indeed, type 2 diabetic patients with serum triglycerides above 2.3 mmolal have a 2-fold increased risk of CHD.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Indeed, type 2 diabetic patients with serum triglycerides above 2.3 mmolal have a 2-fold increased risk of CHD. 4 Elevation of triglyceride levels in type 2 diabetes results mainly from an overproduction of VLDL triglyceride. 29 Prospective studies have suggested that low levels of DHEAS and DHEA predict the occurence of CHD in men.…”
Section: Discussionmentioning
confidence: 99%
“…O encontro de um efeito independente para as variáveis hábito de fumar, história de hipercolesterolemia e história de hipertensão arterial estão em consonância com os resultados apontados na literatura, sendo considerados os mais importantes fatores de risco para a DIC 4,9,14 . Tais achados implicam no reconhecimento de um contexto multifatorial para a DIC, recomendando a implementação de Ações de Saúde direcionadas para a prevenção e controle simultâneos de tais fatores de risco.…”
Section: Discussionunclassified
“…14 It is currently unknown, however, whether these defects are inherent features of type 2 diabetes or secondary to metabolic alterations such as chronic hyperglycemia, 15,16 increases in free fatty acid (FFA) concentrations, [17][18][19][20][21] or other lipid abnormalities. 18,22,23 Regarding insulin, acute studies have shown that although physiological changes in circulating insulin concentrations do not alter blood flow, they potentiate ACh-induced vasodilatation. 24 The only treatment study hitherto performed in type 2 diabetes examined effects of antioxidants on endothelial function.…”
mentioning
confidence: 99%